Performance indicators for management and benchmarking of sewerage services - a case study in Klang Valley / Siti Rashidah Mohd Nasir, Prof Madyair Dr Suhaimi Abdul Talib and Prof Madya Ir Dr Aminuddin Mohd Baki - Mohd Nasir, Siti Rashidah; Abdul Talib, Suhaimi (Prof Madya Dr); Mohd Baki, Aminuddin (Prof Madya Ir Dr) (2006)
Performance Indicator (PI) and Benchmarking have been widely used in measuring performance of management areas. In light of this, the use of PI and Benchmarking has now being extends to sewerage services. PI system is introduced to sewerage services area in order to provide objective and comprehensive management tools for utilities and stakeholder who involved in any aspect of sewerage services. By having the PI and Benchmarking system, the operators may assess their company's performance by comparing its own characteristics with industry-wide standards and targets, hence corrective measures could then be taken to improve performance where appropriate. Performance Indicator (PI) established for sewerage services industry in Malaysia which may assist the Operators to manage their facilities and resources towards providing a more efficient and effective service to all users. The PI will also be useful to Regulators for benchmarking purposes. The sewerage services in Malaysia are currently being managed by Indah Water Konsortium (IWK) and their activities are being regulated by Departrment of sewerage Services (DSS). This research presents the indicators recommended in evaluating the performance of sewerage system in Malaysia that is operated by IWK. The use of the recommended PI will be illustrated in a case study on an activated sludge type wastewater treatment plant, highlighting how the operators can focus their limited resources into areas that will result in higher efficiency and effectiveness.